THE INFLUENCE OF SERVICE INNOVATION, POLICY AND SUPERVISION ON TAXPAYER COMPLIANCE - Ekawati; Salju; Goso; Rahmawati (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This research aims to analyze the influence of service innovation, policy and supervision on taxpayer compliance in East Luwu Regency. Even though East Luwu Regency has large tax potential, the realization of PAD from the tax sector is still not optimal. Tax service innovation, effective tax policies and strict tax supervision are important factors that are expected to increase taxpayer compliance. This research problem examines the influence of tax service innovation, tax policy, and tax supervision on taxpayer compliance in Malili Regency. The phenomenon of low levels of taxpayer compliance in Malili Regency shows that there is an urgent need to evaluate and improve service systems, policies and tax supervision. This research is quantitative research with a descriptive and associative approach, the population of this research is taxpayers in Malili District. East Luwu. The research sample used a non-probability sampling technique by determining the sample using the MoE formula so that a sample size of 100 respondents was obtained. Data was collected through a questionnaire that had been tested for validity and reliability, the data was tested using the SmartPLS statistical tool. The research results show that tax service innovation and tax supervision have a positive and significant effect on taxpayer compliance. Tax policy has a positive but not significant effect on taxpayer compliance. Simultaneously, these three factors in an integrated and sustainable manner can increase taxpayer compliance in Malili, East Luwu Regency.